P008 IMPACT OF A MULTIDISCIPLINARY E-BOARD FOR COMPLEX INFLAMMATORY BOWEL DISEASE MANAGEMENT. (7th February 2019) - Quinn, Kevin P; Prothero, Breanne; Russell, Jennifer M; Hegge, Ryan; Bormann, Alexander von; Larson, Putchalee; Christofferson, Sara; Smyrk, Thomas; Mathis, Kellie L; Goenka, Ajit; Sheedy, Shannon; Fletcher, Joel G; et al.
Abstract: Background: Managing patients with inflammatory bowel disease (IBD) in the modern era requires an interdisciplinary approach among a wide range of specialties with expertise in IBD. However, specialty IBD care is not available at all medical institutions. We herein assess the impact of a biweekly multidisciplinary IBD case conference at a tertiary referral center that incorporates videoconferencing to community-based centers (IBD eBoard) on the management of complex IBD cases. Methods: From February 2017 through October 2018, data was collected prospectively during each IBD eBoard conference. Collected data included the number and role of internal attendees, the number of external attendees (via videoconferencing), external attendee site, case presenter, presented case diagnosis, and specific question(s). Outcomes of the discussion were then recorded, including if the initial diagnosis was changed and any recommended testing, medical, and surgical treatments Results: Since its inception in February 2017, a total of 34 IBD eBoard conferences have taken place, with an average of 18.8 internal attendees and 5.6 external attendees from 6 community-based centers, including one in China. Attendees have included gastroenterologists, colorectal surgeons, radiologists, pathologists, nurse practitioners, fellows, residents, and study coordinators, among others. In total, 85 individual cases were presented (4 cases presented a second time and 1 case presented a third time). Six cases were presented externally via videoconference technology, with a community hospital in China being the furthest location geographically. Of the 85 new cases presented, the initial diagnosis was changed in 8 (9.4%). Recommendations for further diagnostic testing were made in 41 of the 90 presented cases (45.6%), while recommendations for changes in medical and surgical IBD management were made in 60 (66.7%) and 45 (50%) cases, respectively. Discussion: Our IBD eBoard offers a unique opportunity for improving the care of complex IBD patients by combining the multidisciplinary expertise of a tertiary referral IBD center with videoconference technology to allow for outreach consultation to smaller, community-based centers. Through collaborative discussion, this approach appears to significantly impact the management of presented cases. This model is likely easily reproducible among other IBD centers. To implement more widely, further work is necessary to determine the long-term impact and cost-effectiveness of such an approach.